Effects of the DEFB1-20G>A and DEFB1-52G>A gene polymorphism on the level of beta 1 defensin (DEFB1) in young adults with community-acquired pneumonias - B. T. Zagalaev; N. A. Miromanova; A. M. Miromanov (Медицинская иммунология)
The purpose of the present study was to evaluate the effect of DEFB1-20G>A and the DEFB1- 52G>A gene polymorphisms on the expression of DEFB1 in military-age patients with a history of communityacquired pneumonia. A survey of 160 unrelated patients of military age (18-20 years), Caucasian origin was carried out. The first group (n = 80) included the patients with COVID-19 infection complicated by mild pneumonia (n = 40) and severe pneumonia (n = 40). The second group was taken for clinical comparison (n = 80) included the patients with acute respiratory infection (ARI) of non-influenza etiology, complicated by mild pneumonia (n = 40) and severe pneumonia (n = 40). The control group consisted of 86 practically healthy men of the same age. Exclusion criteria were as follows: presence of family relations; patients with acute and/or chronic concomitant pathology. Research methods included clinical laboratory techniques (immunological testing of DEFB1 using a set of ELISA reagents Cloud-Clone Corp. (USA); genetic (polymorphism of the DEFB1-20G>A gene, DEFB1-52G>A gene) with standard primer sets of Litech-SNP (Russia); instrumental examination (computed tomography). The studies were carried out upon admission to the hospital. Statistical evaluation was carried out using the IBM SPSS Statistics Version 25.0 software package (IBM, USA). Predominance of -20A- alleles and genotypes was established -20A/A and -52A/A of the DEFB1 gene variants in the patients with development of severe pneumonia associated with COVID-19 infection. There was an increase in the DEFB1 content in the group with COVID-19 infection by 1.1 times compared with the ARI group, and a 1.5-fold increase against the control group. The changed levels of DEFВ1 associated with severity of community-acquired pneumonia were also characterized by its 1.7-fold increase in the group with a severe clinical course in presence of COVID-19 infection, and by 1.2 times in patients with ARI. The DEFB1 concentration increases significantly in the carriers of DEFB1 -20A/A and -52A/A genotypes. In patients of military age with community-acquired pneumonia, an increased concentration of DEFВ1 is registered, with highest values observed in the group with severe pneumonia due to COVID-19. Carriage of -20A/A and -52A/A genotypes of DEFB1 gene is associated with increased contents of DEFB1. Presence of -20A alleles, -20A/A, and -52A/A genotypes of the DEFB1 genes is associated with severe community-acquired pneumonia associated with COVID-19 infection in patients of military age.